2019
DOI: 10.3390/environments6010007
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Water Quality of a Tropical Reservoir

Abstract: A study of the water quality of the Adolfo López Mateos Reservoir (ALMD) was developed through different indicators from a spatial and seasonal perspective. Variables related to the general characteristics of water quality, trophic level, and ecological risk were assessed through the National Sanitation Foundation–Brown Water Quality Index (WQINSF–BROWN), the Carlson Trophic State Index (TSICARLSON) and the Håkanson Ecological Risk Index (RIHÅKANSON). Using data from physical, chemical, and biological paramete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
2
4
0
3
Order By: Relevance
“…These results were very similar to those reported by Mazhan and Makhlougl [22] and Vidović et al [2]. Similar results have also been published by Quevedo-Castro et al [48].…”
Section: Trophic Status Of the Reservoirsupporting
confidence: 92%
See 2 more Smart Citations
“…These results were very similar to those reported by Mazhan and Makhlougl [22] and Vidović et al [2]. Similar results have also been published by Quevedo-Castro et al [48].…”
Section: Trophic Status Of the Reservoirsupporting
confidence: 92%
“…The Carlson Modified Trophic State Index indicated that the trophic state of the ALM reservoir was mesotrophic (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). This conclusion was based on the nitrogen, phosphorous, and chlorophyll-a concentrations and Secchi disk depths measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrological and climatological features of the study area generate water quality variations in water bodies [45]. Therefore, these characteristics were also studied.…”
Section: Hydroclimatological Conditionsmentioning
confidence: 99%
“…Para el gobierno federal y estatal, es difícil controlar esta contaminación porque proviene de escurrimientos superficiales y no existe industria, finca o municipio que vierta sus desechos en la Presa Adolfo López Mateos (Quevedo-Castro et al, 2019). Los principales contaminantes de la presa son material orgánico biodegradable, contaminación fecal difusa y material particulado disuelto que provoca variaciones en la turbidez del agua (Quevedo-Castro et al, 2019). Se trata de una contaminación normal que se produce por los escurrimientos superficiales de las inmediaciones de la Presa Adolfo López Mateos.…”
Section: Contaminación Del Agua En La Presa Adolfo López Mateosunclassified